The Secret Sauce: How Developmental Relationships Shape the Leadership Journeys of Women Leaders in Christian Higher Education. Issue 1 (1st January 2019) - Longman, Karen A.; Drennan, Amy; Beam, Julie; Marble, Amanda F.
Abstract: Although women are now graduating in greater percentages then men at all degree levels—associate through doctorate—the senior-level leadership on most postsecondary campuses in the United States continues to be predominantly White and male. Numerous internal, institutional, and systemic barriers have been identified that hinder women from aspiring to leadership and advancing into senior-level roles. However, new streams of research in the leadership literature are addressing the motivations, encouragers, and discouragers that influence women's leadership aspirations and experiences, including a growing body of scholarship focused on the process of leadership identity development rather than simply leadership development . This article presents the relevant literature and discusses the findings of interviews with 30 emerging and current women leaders in the Council for Christian Colleges & Universities; the interview questions focused on the extent to which various kinds of developmental relationships (specifically mentoring, coaching, and sponsorship) have been experienced by the participants. Three primary themes emerged from the data analysis of developmental relationships vis-à-vis the participants' leadership journeys: (a) the value of having a network of influential relationships was key in the leadership journey; (b) the perceived benefits of distinct developmental relationships, either present or desired; and (c) the contribution of developmental relationships in navigating women leaders' professional challenges. Although many of the 30 participants reported having benefited from mentoring of various types in the past, only a few reported having been coached or sponsored. Notably, such developmental relationships were not only desired but also viewed as potentially critical to professional advancement. Recognizing that the influence of developmental relationships (particularly coaching and sponsorship) in later career stages merits greater research attention, this article proposes a slightly modified version of a Women's Leadership Development Model in which developmental relationships are recognized as a motivator for women to aspire to or step into leadership, with coaching and sponsorship playing a larger role in the later stages of women's career development.